Effect of Financial Literacy on the Financial Behavior of the Millennial Generation about the Dangers of Fraudulent Investment and Flexing Affiliations - Indratirta, Nadia Prima; Handayati, Puji; Juliardi, Dodik (PT. Riset Press International, 2023)
This research presents insights into the impact of fraudulent investments spread by irresponsible influencers and affiliates on the millennial generation in Malang City. In addition, this study aims to determine the effect of financial literacy on the financial behavior of millennials in the city. This study uses a quantitative approach with descriptive analysis to explain the relationship between financial literacy variables and financial behavior. The main data was collected through an online survey with questionnaires distributed through social media platforms as well as through in-depth interviews with respondents who had been victims of fraudulent investments. The results showed that financial literacy has a significant effect on the financial behavior of the millennial generation in Malang City. Millennials with a high level of financial literacy tend to show better financial behavior, including in money management, investment, and debt management. It is hoped that the results of this study can raise awareness about the importance of financial literacy and help millennials make wise financial decisions